2021
DOI: 10.1007/s00380-021-01827-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical outcomes and left ventricular remodeling after ST-elevation myocardial infarction between patients with and without diabetes mellitus

Abstract: Left ventricular remodeling (LVR) after ST-elevation myocardial infarction (STEMI) is generally thought to be an adaptive but compromising phenomenon particularly in patients with diabetes mellitus (DM). However, whether the extent of LVR is associated with poor prognostic outcome with or without DM after STEMI in the modern era of reperfusion therapy has not been elucidated. This was a single-center retrospective observational study. Altogether, 243 patients who were diagnosed as having STEMI between January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Previous studies demonstrated that adverse remodeling was associated with increased incidence of HF [ 2 , 28 ] as well as overall MACE [ 29 ]. In a prospective cohort of 285 patients with STEMI who underwent revascularization, developing adverse LV remodeling at 6 months, defined as ≥ 12% increase in both LVESV and LVEDV by CMR, was associated with higher 5-year composite of all-cause death and HF hospitalization [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that adverse remodeling was associated with increased incidence of HF [ 2 , 28 ] as well as overall MACE [ 29 ]. In a prospective cohort of 285 patients with STEMI who underwent revascularization, developing adverse LV remodeling at 6 months, defined as ≥ 12% increase in both LVESV and LVEDV by CMR, was associated with higher 5-year composite of all-cause death and HF hospitalization [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of quantity, some reports showed the ratio of 2-vessel disease in STEMI patients with DM was similar with nonDM (36% vs 35%, P = 0.809), but 3-vessel disease was different obviously (29% vs 23%, P = 0.121) [19]. Other study showed 2-vessel disease (31.6% vs 27.6%, P not displayed) and 3-vessel disease (24.5% vs 15.2%, P not displayed) of STEMI + DM patients were similar with patients with nonDM [20]. Another study showed 2-vessel disease (31.0% vs 28.0%, P not displayed) and 3-vessel disease (28.0% vs 16.0%, P not displayed) of STEMI + DM patients were higher than that of nonDM [21].…”
Section: Diatebes and Coronary Arteriesmentioning
confidence: 72%
“…In terms of complexity, baseline SS of STEMI + DM patients was higher than nonDM patients (18.0 ± 11.5 vs 15.0 ± 12.5, P = 0.013) in Burgess et al study [20]. MVD-STEMI + DM patients are more severe than STEMI + DM patients, but there are no reports on the speci c situation of SYNTAX score.…”
Section: Diatebes and Coronary Arteriesmentioning
confidence: 88%
See 1 more Smart Citation
“…Although we found no correlation between plasma miR-22 and glycemia, the diabetic status per se impacts the ability of miR-22 to discriminate between aMI patients and controls. In patients with HF and aMI, DM was shown to influence LVR and LV dynamics, with a consecutive impact on their cardiovascular outcome [ 44 , 45 ]. Of note, in these patients, HbA1c values correlate negatively with the LVEF and strongly predict both short- and long-term complications [ 46 , 47 , 48 ].…”
Section: 1 Mir-22 and The Stressed Heartmentioning
confidence: 99%